Gender Differences in Cooperation: Experimental Evidence on High School Students - José Alberto Molina; J. Ignacio Giménez-Nadal; José A. Cuesta; Carlos Garcia-Lazaro; Yamir Moreno; Angel Martínez Sánchez (Institute for the Study of Labor (IZA), 2013)
Charles Darwin (1874) stated that women are less selfish but men are more competitive. Very recent papers (Eckel & Grossman, 1998, 2001 or Andreoni and Vesterlund 2001, among others) have shown the relevance of gender in altruism in both ultimatum and dictator games. In this paper we analyze the role of gender in repeated Prisoners' Dilemma played by Spanish high-school students in both a square lattice and a heterogeneous network. We find that female students have a higher probability of cooperation than male students.
Keywords: C72; C73; C93; D03; J16; 330; gender differences; cooperation; high school students; prisoners' dilemma